Habitat Preference and Abundance of Mole Crab Based on Sea Tides in Coastal Area of Kebumen Regency - Desi, Tri (AQUASAINS, 2020)
Mole crab is an important resource in the food chain cycle and an initial level consumers in sandy areas. Mole crab lives in the swash zone that is affected by sea tides. Comparison of habitat and abundance of each station based on tides in terms of the type of utilization of the study location. The purpose of this study was to determine the abundance at high tide and low tide, species, and habitat preferences of mole crab, also to determine the relationship between their habitat preferences and their abundance. The method used in this study was descriptive exploratory and uses purposive random sampling technique. Abundance data collection was done by using a 10 x 10meter transect quadrant at two spring tides and two neap tides in the swash zone area. The results showed that the abundance of mole crab at high tide was 214 - 239 ind/100m2 and at low tide was 378 - 509 ind/100m2. There are three types of mole crab that has been found, Emerita emeritus, Hippa adactyla and Albunea symmysta. Favored habitat of mole crab in coast area of Kebumen Regency has a flat to sloping beach, wide swash zone at high tide 14.5 - 24.5m, and at low tide is 20 - 32.5m, medium sized beach sand (0.25-0.5mm), and has low organic material values. The results of the PCA (Principal Component Analysis) analysis that the sediment grain size and the width of the swash zone have a positive correlation with the abundance of mole crab.